The Role of Digital Marketing and Promotion in the Business Performance of Small and Medium Enterprises (SMEs) in Developing Countries - Mahaliani, Eva; Kurniawati; Masnita, Yolanda (Jurnal Economic Resource, 2025)
This study examines the role of digital marketing and promotion in the business performance of small and medium-sized enterprises (SMEs) in developing countries, particularly Indonesia. In the face of intense competition, SMEs are required to leverage digital media to sustain and grow their businesses. The objective of this study is to comprehensively investigate how digital marketing capabilities and their adoption through promotions can enhance SME productivity. Additionally, this research analyzes the impact of customer relationship orientation and technology orientation on SME business performance in developing country markets. The research method uses cross-sectional data obtained through a questionnaire distributed via Google Forms on social media to SME owners in Indonesia who have started their businesses within the past year. The findings reveal that competition intensity has a significant influence on promotion. Furthermore, customer relation orientation and technology orientation have a significant influence on digital marketing capability. Additionally, digital marketing capability and promotion have a significant influence on business performance.